Herzen’s Interpretation of Religion as an Illusion of Open Philosophy: Taking into Account the Research Perspective in Poland - Uglik, Jacek (Sensus Historiae, 2025)
Herzen’s critical analysis of religion and religiousness of man allows one to better understand his anti-dogmatic intellectual stance, dubbed here as open philosophy. The article shows Alexander Herzen as opposing any type of religion, understood broadly as any set of beliefs (not necessarily relating to the transcendent sphere) that stifles individual freedom and is, in effect, an illusion of open philosophy. All religiousness is connected with the notion of a dogma; yet, Herzen claimed in addition that “there would be no freedom in the world unless religion and politics become a simple human matter, open for criticism and rejection.” The article also aims to show that Herzen’s ideas revolve around the place of women in the world organised by religion and, thus, that Herzen’s 19th century contribution is an important voice in the debate on the emancipation of women. The overall conclusion stemming from the arguments presented in the article is that there exists a clearly emerging tension between Herzen and religion. The open philosophy, as presented by Herzen, is at the same time areligious and explorative.